Acrylic external skeletal fixator for the treatment of long bone fracture in dogs - Julie B (Department of Veterinary Surgery and Radiology, College of Veterinary and Animal Science, 2005)
The efficacy of replacing stainless steel connecting bar in external skeletal fixator (ESF) with acrylic connecting bar was evaluated by using acrylic connecting bar in twelve clinical cases of complete fracture of long bones in dogs presented to the Surgery Units of Veterinary Hospitals of Mannuthy and Kokkalai, College of Veterinary and Animal Sciences, Mannuthy, during the period of December 2003 to May 2005. All the animals were subjected to detailed clinical, radiological, haematological and serum biochemical evaluations before application of acrylic fixator and also postoperatively at two weeks interval upto sixth week or until the removal of the implant. Type IA or type II acrylic fixators were applied by closed or open approach under general anaesthesia depending on the type of fracture. Transfixation pins were drilled and the acrylic connecting bar was connected directly or following the application of a temporary stainless steel connecting bar, which was removed later. Fixator with acrylic connecting bar on one side and stainless steel connecting bar on the other side was used in three animals. Acrylic external fixator proved to be an economical, technically feasible, clinically successful and reliable alternative for stainless steel external fixators for the immobilization of fractures of radius and ulna and tibia and fibula in animals of less than 15 kg body weight. In heavier animals, usage of acrylic bar on one side of the type II fixator gave adequate stability in case of radial fractures but not for tibial fractures. Early return of sound functional limb usage following fixation with acrylic ESF was remarkable. All the animals, except three, could make slight ground contact with the fractured leg by the third post operative day and had apparently normal gait by the fourth week of observation with full weight bearing on the limb. Loosening of the proximal most pin occurred in Case Nos. 2, 3 and 4, by fourth week of observation, where type I acrylic fixator was used, but none of them affected the fracture healing significantly. Breakage of acrylic bar occurred in Case Nos. 7 and 9. In Case No. 7, the acrylic bar failed to tolerate the strong muscle pull on the fractured femoral fragments and in Case No. 9 severe mutilation by the animal resulted in breakage of the bar. Four animals exhibited mutilation on the implant, but only one on them showed severe mutilation. Mild pin tract drainage occurred in four animals and pin tract sepsis resulted in one animal. The heat generated during exothermic phase of acrylic hardening produced no apparent thermal necrosis of bone or soft tissue. Mild to moderate degrees of malalignment occurred following application of acrylic fixator in Case Nos. 3, 5, 6 and 11, which got nullified with progressive callus formation and resulted in restoration of normal straight line alignment of the bone. Marked angulation of the bone fragments occurred in Case Nos. 2 and 9. The fracture gap in all the cases was found to be progressively getting filled up with callus. Rate of callus formation varied with age of the animal, type of fracture and stability of the apparatus. In 50% of the cases, the fracture healed with endosteal callus only, while it healed with endosteal and periosteal callus in rest of the animals. Periosteal reaction of varying degree occurred in most of the cases but did not affect fracture healing or functional limb usage. Osteolysis was noticed around proximal pin tract in four animals, which could be due to loosening of pins. However, no significant alteration in fracture healing was produced. Acrylic column of one centimetre diameter was found sufficient for use as connecting bar of ESF for immobilization of fractures of radius and ulna and tibia and fibula in animals of less than 15 kg body weight.